Aplicação da técnica PCR para detecção de bactérias potencialmente patogênicas em um sistema UASB-lagoas de polimento para tratamento de esgoto doméstico - Fernanda Maria Santos do Nascimento (2008)
Wastewater treatment based on a UASB reactor followed by polishing ponds is well established for removing organic and inorganic matter, as well as pathogenic microorganisms. Usually the evaluation of pathogenic bacteria removal in wastewater treatment systems is carried out by analyzing fecal coliforms and Escherichia coli decay. Recently moleculartechniques based on polimerase chain reaction method (PCR) have been applied for detecting pathogenic bacteria in water, food and clinical samples. The present work aimed to establish a methodology for sample preparation, DNA extraction and PCR analysis in samples along the UASB- polishing ponds system for several pathogenic bacteria. Monitoring of Escherichia coli, Salmonella spp., Salmonella thyphimurium, Shigella spp., Shigella dysenteriae, Helicobacter pylori, Enterococcus spp., e Staphylococcus aureus were performed by PCRusing specific primers. It can be concluded from results obtained in this research that Escherichia coli, Enterococcus spp and Shigella dysenteriae were detected in the raw sewage and were removed along the UASB- polishing ponds system since they were not detected inthe final effluent. On the other hand, DNA from Salmonella typhimurium was detected only in the effluent from polishing ponds and in the final effluent. Helicobacter pylori e Staphylococcus aureus were not detected in any analyzed samples. The results obtained here show the applicability of PCR method for monitoring pathogenic bacteria in wastewater systems